1991
DOI: 10.1002/eji.1830211222
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation by tumor necrosis factor‐α of neutrophil cell surface expression of the sialophorin CD43 and the hyaluronate receptor CD44 through a proteolytic mechanism

Abstract: Adhesion of human neutrophils to endothelial cells is a crucial step during migration to the extravascular sites of inflammation. A large number of molecules, including the CD44 and LAM-1 antigens, have been described to participate in this process. We have investigated the regulation by human recombinant tumor necrosis factor-alpha (TNF-alpha) of human neutrophil plasma membrane expression of both CD44 and LAM-1 adhesion molecules, as well as that of CD43 sialophorin, which has been involved in adhesion and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 29 publications
5
56
1
Order By: Relevance
“…This antigen down-regulation is triggered by several physiological neutrophil activating agents, and correlates well with the previously reported proteolytic down-regulation of other glycoproteins, CD43 and CD44 [35].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This antigen down-regulation is triggered by several physiological neutrophil activating agents, and correlates well with the previously reported proteolytic down-regulation of other glycoproteins, CD43 and CD44 [35].…”
Section: Introductionsupporting
confidence: 90%
“…In this context, proteolytic modulation of membrane proteins is becoming an important regulatory mechanism in cell biology. This proteolytic downregulation has been shown on an increasing number of proteins, including some cytokine receptors such as tumor necrosis factor ␣ (TNF-␣) receptor and interleukin-6 (IL-6) receptor [30], Fas ligand [31], adhesion molecules such as L-selectin [32,33], ICAM-3 [34], CD43, and CD44 [35]. Specific proteases are present on the cell surface to specifically activate the thrombin and plasminogen systems [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…PMN activation is most likely initiated by multivalent interactions of bacterial adhesins with either sialo-or asialo-forms of leukosialin or leukocyte common antigen in a manner analogous to the triggering effects of crosslinking CD43 or CD45 on PMNs by specific MAbs (25,27,39). Activation of PMNs by anti-CD43 antibodies is accompanied by proteolytic cleavage and shedding of the CD43 extracellular mucinlike domain (3,6,46). It remains to be determined whether shedding of CD43 from PMNs occurs in response to adhesion of S. gordonii or A. naeslundii and conversely, whether shedding of CD43 from PMNs, induced by anti-CD43, affects subsequent adhesion and lectinophagocytosis of these bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that shedding of various cell surface proteins can be induced by external stimuli such as crosslinking (43), or by internal activation of signaling pathways, especially those mediated through PKC (16,18,44). Therefore, it was of interest to determine and compare the effects of bivalent F(abЈ) 2 and monovalent Fab of IM7, and those of the PKC activator PMA, on CD44 shedding.…”
Section: Cd44 Shedding From Msf Cultured On Immobilized Monovalent Ormentioning
confidence: 99%